ABOUT THE FACTORS AND REASONS OF UNIVERSITY STUDENT EXPULSIONS AND STUDENT MOTIVATION FOR EDUCATIONAL ACTIVITIES - N. G. Osipova; G. V. Kolodeznaya; A. N. Shevtsov (Russian State Vocational Pedagogical University, 2018)
Introduction.The conclusion of the "effective contract" with teachers has recently become one of the innovations at the higher school. According to the drafters of this document, it has to take the position of the economic instrument for increasing the labour productivity of educators and stimulating them to the effective result-oriented activity. However, some qualitative and quantitative indicators of the contract which form the basis of the fixed amount of financial award of teachers lead to confusion. In particular, the number of the students expelled from higher education institution belongs to such indicators.Aim. Based on the factual material, statistical data and mathematical calculations, the aim of the publication is to prove the absence of direct relationship between the number of the expelled students and the quality of professional activity of the university teacher.Methodology and research methods. In the course of the research, the review and synthesis of the scientific publications on the discussed problems were used; poll and questioning of students were conducted by means of the T. I. Ilyina's technique "Motivation for Training in Higher Education Institution". The obtained data was processed by the method of the correlation analysis; degree of statistical reliability of results was estimated by means of calculation of F-criterion.Results and scientific novelty. The survey was conducted among full-time students of different years of studies enrolled on the five-year specialty training programme "Train Traffic Management Systems" of the Far Eastern State Railway Communications University. The survey made it possible to identify the common factors and reasons of expulsion from higher education institution among students of all years of studies. Statistical data on motivation of students for training are collected and analysed. Correlations between indicators of expulsion and motives to get higher education are established. The authors provided a reasoned justification for obvious absurdity of the issue about accounting the student contingent retention as criterion of the teacher quality of work. Student expulsion is the indicator that reflects a condition of all education system and includes the following: school, institute of the Unified State Examination (USE), selection criteria in higher education institution, standard legislative base in education, curricula, logistics and equipment, conditions of educational activity, etc., as well as student motivation for training. Therefore, the ordinary teacher can not and must not be responsible for student expulsions.Practical significance. The authors conclude that the "effective contract" as it drafted encourages not teachers, but a high number of uneducated "professionals" who graduate from higher education institutions, including those who study free of charge. Artificial support of student membership completely contradicts state policy on human resource development of the country; furthermore, it poses threat of destruction both for the system of the higher education, and for national economy in general. It is obviously required to develop other more reasonable approaches that are adequate to the higher school tasks and to the choice of quality criteria for activity of higher education institutions and their employees.